Magnetostimulation in complex treatment of venous leg ulcers - Pasek, Jarosław; Szajkowski, Sebastian; Cieślar, Grzegorz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
A significant health problem in many countries around the world is the occurrence of difficult-to-heal wounds of various etiologies, including leg ulcers. The tendency to recurrence requires frequent hospitalization and long-term medical care. In medicine, physical medicine procedures are increasingly being used in the comprehensive treatment of chronic wounds, thus expanding the range of therapeutic options. The article presents the results of the treatment of a 70-year-old patient with venous leg ulcer who, regardless of routine treatment (pharmacotherapy, dressings, compression therapy), received magnetostimulation treatments using an alternating magnetic field with a low induction value. The comprehensive treatment supported by physical procedures resulted in complete healing of the ulcer, reduction in the intensity of inflammation in the tissues surrounding the ulcer and alleviation of pain ailments.